Territorial Concentration of Homicides, Kidnappings, and Extortions: The Case of the Metropolitan Region of Santiago, Chile; Concentración territorial de Homicidios, Secuestros y Extorsiones: El caso de la Región Metropolitana de Santiago de Chile - Dammert-Guardia, L (Centro Estudios Derecho Penal, 2025)
This article provides evidence on the expansion of organized crime in Chile from a territorial perspective, employing Bergman’s theory of criminal violence equilibria3. It examines the Santiago Metropolitan Region, which displays equilibria characterized by low criminality, suggesting that the spatial concentration of homicides, kidnappings, and extortions correlates with the presence of high-criminality equilibria. Using a mixed-methods approach, the study presents evidence linking homicides, on one hand, and kidnapping and extortion phenomena, on the other, within specific sociodemographic contexts. It proposes an analytical framework for interpreting violent crimes predominantly associated with organized crime, emphasizing the need for tailored public policies sensitive to territorial differences. Additionally, the article highlights the necessity for further research into these relationships to better understand criminal dynamics, particularly those linked to organized crime. © (2025), (Centro Estudios Derecho Penal). All Rights Reserved.